Enhancing Speaking Proficiency Through Interactive Video Media: Material Development - Halimatussa’diyah, Halimatussa’diyah; Hartono, Hartono; Sudiran, Sudiran (STKIP Singkawang, 2024)
The purpose of this study is to assess the needs of students and teachers for improving speaking abilities and to validate the usage of interactive video in the classroom. The ADDIE model's research and development (R&D) methodology was employed in this study: analysis, design, development, implementation, and assessment. As a result, it validated the teacher's material requirements while also analyzing the students' demands. Three English teachers and 18 secondary school students from MTS Miftahul Ulum Lumajang participated in this study. Data for this study were gathered through class observation, interviews, and questionnaires. An interview, however, revealed that the teacher frequently experienced difficulties developing English material for the junior high school class, notably for the eighth grade, due to students' questions and opinions. A questionnaire survey found that the majority of teachers (66.7%) had trouble improving pupils' speaking abilities by asking and providing opinions. According to this survey's findings, most students (72.2%) struggle to improve their speaking skills through questioning and replying. As a result, interactive video must be used. This study has given the majority of teachers a favorable impression of the efficiency of interactive movies in improving speaking proficiency.